PENGARUH MOTIVASI DAN KEDISIPLINAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI KECAMATAN JANGKAR KABUPATEN SITUBONDO - Senain Senain; Arif Windana Agustira (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Abdurachman Saleh Situbondo, 2017)
The purpose of this study is to know about how Employee Productivity and factors - factors that affect the Motivation and Discipline in the District of Jangkar Situbondo District. Techniques of making data using obesrvasi techniques, interviews or interviews, and media questionnaires by selecting informants who use and issue information technically and functionally. The data obtained were analyzed qualitatively and supported by quantitative data. The result of this research is leadership style and organizational culture on employee performance, especially in the field of human resource development, done in accordance with existing rules and regulations that have been determined by looking at some indicators of Motivation (X1), Discipline (X2) and Working Employee Productivity (Y). The analysis is Multiple Regression Analysis. Hypothesis testing is done by using Test t and Test f. The object of research in this research is the population of District of Jangkar Situbondo Regency, with the number of respondents as many as 29 people. The results showed that the motivation in the District Office of Jangkar Situbondo Regency has not been effective, while the discipline of Sudang effective because it has a significant effect on Work Productivity Employees.